Effects of Different Amendment Materials on Reclaimed Soil Structure and Organic Matter Content of Hollow Village in Loess Region - Liu Zhe; Wang Huanyuan; Sun Yingying; Sun Zenghui; Zhang Ruiqing (Shuitu baochi tongbao)
[Objective] The poor structure and low fertility of reclaimed soil of abandoned homesteads in hollow villages in the loess area were addressed in order to provide a theoretical basis for improving the quality of reclaimed soils. [Methods] The effects of six different treatments of modified materials on structural stability and soil organic matter (SOM) of a reclaimed soil were compared with a control (CK) treatment in a five-year field experiment. The modified materials treatments were maturing agent (TM), fly ash (TF), organic fertilizer (TO), maturing agent + fly ash (TMF), maturing agent + organic fertilizer (TMO), and fly ash + organic fertilizer (TFO). [Results] SOM content was significantly increased (compared with CK) after the application of the different modified materials that promoted the cementation and aggregation of water-stable microaggregates (<0.25 mm) into water-stable macroaggregates (>0.25 mm). The content of water-stable macroaggregates showed an increasing trend. In the 0—15 cm soil layer, the contents of water-stable macroaggregates under TM, TF, TO, TMF, TMO, and TFO were increased by 328.2%, 130.0%, 87.8%, 81.1%, 36.7%, and 12.2%, respectively, compared with CK. Moreover, the application of the TF, TO, TMF, TMO, and TFO treatments significantly increased the mean weight diameter (MWD) and geometric mean diameter (GMD) of soil aggregates, while the unstable-aggregate index (ELT) and fractal dimension (D) were decreased (p<0.05). SOM content was significantly positively correlated with MWD, GMD, and >2 mm water-stable aggregates, and significantly negatively correlated with the ELT, D, and water-stable microaggregates. In particular, reclaimed soil under TFO had the highest content of SOM and water-stable macroaggregates, and the best effect on improving soil structrual stability. [Conclusion] Using a combination of organic fertilizer and fly ash is an appropriate practice to improve reclaimed soil structure and fertility of abandoned homesteads in hollow villages in the loess region.